Intestinal Microbiota and the Innate Immune System – A Crosstalk in Crohn’s Disease Pathogenesis - Haag, Lea-Maxie; Siegmund, Britta (Frontiers in Immunology, 2015)
Crohn’s disease (CD) is a chronic, relapsing inflammatory disorder that can occur anywhere along the gastrointestinal tract. The precise aetiology of CD is still unclear but it is widely accepted that a complex series of interactions between susceptibility genes, the immune system and environmental factors are implicated in the onset and perpetuation of the disease. Increasing evidence from experimental and clinical studies imply the intestinal microbiota in disease pathogenesis thereby supporting the hypothesis that chronic intestinal inflammation arises from an abnormal immune response against the microorganisms of the intestinal flora in genetically susceptible individuals. Given that CD patients display changes in their gut microbiota composition, collectively termed ‘dysbiosis’, the question raises whether the altered microbiota composition is a cause of disease or rather a consequence of the inflammatory state of the intestinal environment. This review will focus on the crosstalk between the gut microbiota and the innate immune system during intestinal inflammation, thereby unravelling the role of the microbiota in CD pathogenesis.